Psychological Effort Regulation among Kindergarten Teachers and Its Relationship with Some Variables (Journal of the College of Basic Education, 2026)
The profession of a kindergarten teacher is considered one of the professions most exposed to work pressures, due to the burdens, requirements, and high levels of technical and personal competencies and skills required from the teacher. Accordingly, the current study aimed to identify the regulation of psychological effort among kindergarten teachers and its relationship with some variables. To achieve the objectives of the study, the researcher developed a psychological effort scale for teachers and calculated its validity, reliability, discriminatory power, the one-sample t-test, the independent two-sample t-test with equal sample sizes, and Pearson’s correlation coefficient. The research found statistically significant differences favoring the research sample. No statistically significant differences were found according to the marital status variable, while statistically significant differences were found according to the living situation variable (modern, independent, or extended family). Furthermore, statistically significant differences were found according to the number of children variable (one, two, three, and four children). The researcher recommended strengthening psychological and professional training programs for kindergarten teachers in a way that contributes to developing skills related to the regulation of psychological effort, especially self-regulation skills, stress management, and emotional control during educational work. The study also recommended providing a supportive working environment within kindergartens by enhancing administrative and collegial support, as this plays an important role in maintaining a stable level of psychological effort regulation among teachers. Furthermore, it recommended taking into account family circumstances and housing patterns when assigning job responsibilities to teachers, especially those living in extended families, in order to reduce the exhaustion of psychological effort and to enhance balance between professional and family life. It also recommended encouraging the relevant authorities in the Ministry of Education to include psychological effort regulation skills in pre-service and in-service training programs for kindergarten teachers.